Itraconazole inhibits TNF‐α‐induced CXCL10 expression in oral fibroblasts. (28th February 2014) - Ohta, K; Ishida, Y; Fukui, A; Nishi, H; Naruse, T; Takechi, M; Kamata, N
<x xml:space="preserve">Abstract</x> Objective Itraconazole (ICZ) has a broad spectrum of antifungal activity including a wide range of Candida spp. TNF‐α, an inflammatory cytokine associated with Th1‐mediated oral inflammatory disease, enhances inflammatory mediators, such as CXCR3‐agonistic chemokines including CXCL10. We examined the anti‐inflammatory potential of ICZ against TNF‐α‐induced chemokines in oral fibroblasts. Materials and methods We investigated the effects of ICZ on mRNA expressions of various TNF‐α‐induced chemokines in immortalized oral keratinocytes (RT7) and oral fibroblasts (GT1) using quantitative PCR analysis. Subsequently, the effects of ICZ and fluconazole (FLZ) on TNF‐α‐induced CXCL10 proteins in GT1 and primary fibroblasts were examined using enzyme‐linked immunosorbent assays (ELISA). The effect of ICZ on signal transduction protein phosphorylation involved in CXCL10 production from TNF‐α‐stimulated GT1 was examined by western blotting. Results ICZ inhibited TNF‐α‐induced CXCL10 mRNA in GT1, but not RT7. Although ICZ did not affect TNF‐α‐induced IL‐8 mRNA, the mRNAs of TNF‐α‐induced CXCR3‐agonistic chemokines such as CXCL9 and CXCL11 were inhibited by ICZ in GT1. TNF‐α‐induced CXCL10 protein production in GT1 and primary fibroblasts was inhibited by ICZ, but not FLZ. Finally, ICZ inhibited TNF‐α‐induced phosphorylation of c‐JUN, which is related to CXCL10 production by TNF‐α‐stimulated GT1. Conclusion ICZ may be useful as therapy for Th1‐mediated oral inflammatory disease.